Value of Mangrove And Crab Cultivation Development Patterns in Kaliwlingi Village, Indonesia - Hartanti, Ninik Umi; Fithor, Alin; Suyono, Suyono; Sutaman, Sutaman; Nurjanah, Nurjanah (Jakarta Technical University of Fisheries, 2024)
Both mangroves and crab cultivation contribute to sustainable development and positively impact local communities and ecosystems. Here are some of the values associated with their product. The advantage of this mangrove crab cultivation business can be maximal if the cultivated crabs achieve normal growth and maximum results. The demand for crabs is currently very large in domestic and international markets. Determination of alternative patterns value in aquaculture analysis can be identified in Kaliwlingi Village. The socio-economic value has a new concept between characteristics cultivation with income production costs, a major achievement step in realizing Indonesia's best just and prosperous society.